Studi Penerapan Ekstrak Eceng Gondok Sebagai Inhibitor Korosi Pada Pipa Baja Karbon Dalam Medium Korosi Air Laut dan Air Hujan Dengan Variasi Suhu - Nuringsih, Fadhilla Maharani; Prasojo, Ikhwan Mahendra; Ratnasari, Yuki; Hakim, Muhammad Fahmi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Corrosion is a decrease in the quality of metal due to electronic reactions with its environment or in general it is better known as rusting. When viewed from a chemical perspective, corrosion is a metal reaction that is in direct contact with the environment and oxygen. Corrosion cannot be eliminated, but it can be controlled. So controlling the corrosion rate using organic or inorganic based corrosion inhibitors is appropriate. This research used grade 5L carbon steel pipes and looked at the effect of water hyacinth extract on the corrosion rate. In this research, it was proven that water hyacinth extract contains tannins and saponins which can inhibit the optimal corrosion rate at an extraction temperature of 85ºC. The SEM test in this study showed that the steel pipe samples immersed in the corrosion inhibitor medium had a smoother surface compared to the corrosion medium without inhibitors.